The Effect of Innovation, Brand Image Perception and Promotion on The Decision to Use Arts Tutorial Services - Annisa Rofiatur Rahma Putri Mulyana; Anjar Dwi Astono (Universitas Pelita Harapan, 2025)
The purpose of this study was to analyze the influence of innovation, brand image perception, and promotion on the use of services at Sanggar Seni Annisa Rumpaka. This study uses a quantitative approach with a saturated sampling technique, namely all 110 active participants are considered as respondents. The data collection technique was carried out using a validated and proven reliable Likert scale. The data analysis method used is multiple linear regression to analyze the influence of independent variables (innovation, brand image, and promotion) on the dependent variable (decision to use services) both separately and simultaneously. The results of the study indicate that the independent variables have a statistically significant influence on the opinions of product users. Meanwhile, innovation, brand image perception, and promotion also have a significant influence on the decision to use Annisa Rumpaka Art Studio. This study suggests that studio managers continue to innovate in providing services, increase customer satisfaction through quality and consistency, and improve effective marketing strategies to attract and retain more customers.